Reconnection of MV Microgrid with Universal Grid-forming Inverter-based Resources - Laaksonen, Hannu; Hatziargyriou, Nikos (Institution of Engineering and Technology, 2025)
One concern of typically proposed grid-forming (GFM) inverter-based resources (IBRs) has been the microgrid reconnection i.e. transition from islanded to grid-connected operation. Therefore, this paper presents a case study about medium-voltage (MV) microgrid reconnection with universal frequency-locked-loop (U-FLL) -based GFM IBRs. The main aim of the PSCAD simulations was to find out that what is the maximum allowed voltage phase angle difference before MV microgrid reconnection to maintain stability of U-FLL-based IBRs after the reconnection and how much it is dependent on the simultaneous frequency and voltage magnitude differences. Based on the simulation results, the U-FLL based IBRs have very good voltage phase angle difference ride through capabilities i.e. ±140-180° depending on the case. Paper also proposes one new scheme in which perfectly synchronized reconnection could be always achieved by having U-FLL input of one MV IBR from a utility grid synchronous generator’s rotating speed. In addition, paper presents further modified and improved U-FLL-based synchronization method which is grid-forming for generating IBRs and grid-supporting for IBR-based loads.
Keywords: GFM; IBR; MV microgrid; PSCAD simulations; universal frequency-locked-loop; universal grid-forming inverter-based resources; utility grid synchronous generator; fi=Sähkötekniikka|en=Electrical Engineering|